PENGARUH LOVE OF MONEY , MACHIAVELLIAN, EQUITY SENSITIVITY DAN KNOWLEDGE LEVEL PADA PERSEPSI MAHASIWA AKUNTANSI ATAS PERILAKU ETIS AKUNTAN (STUDY KASUS MAHASISWA AKUNTANSI UNIVERSITAS MUHAMMADIYAH JEMBER) - Amalia, Imelda Nur Imana; Yulinartati, Yulinartati (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This research aims to: 1) Recognize the influence of the Love of Money on accounting students'ethical perceptions; 2) Recognize the Machiavellian influence on students' ethical perceptions; 3) Recognize the influence of equality on students' sensitivity to ethical perceptions; and 4) Recognize the influence of knowledge level on students' ethical perceptions. The Muhammadiyah University of Jember's Faculty of Economics and Business served as the setting for this study. The 2018 accounting class served as the study's sample. Purposive sampling was used to select47 respondents for the samples. The study found that accounting students' ethical perceptions are negatively impacted by their love of money. This indicates that accounting students' ethical perception decreases with increasing love of money. Accounting students' ethical perceptions suffer as a result of Machiavellian. This indicates that accounting students have a lower ethical perception the more Machiavellian they are. Accounting students' ethical perceptions suffer as a result of equity sensitivity. This indicates that accounting students' ethical perception decreases with increasing equity sensitivity. Students' ethical perceptions are negatively impacted by their level of knowledge. This indicates that accounting students' ethical perception decreases with increasing knowledge